The impact of high and low-intensity exercise in adolescents with movement impairment. - Francesca Liu; Martyn Morris; Lisa Hicklen; Hooshang Izadi; Helen Dawes (PLoS ONE, 2018)
Five to six percent of young people have movement impairment (MI) associated with reduced exercise tolerance and physical activity levels which persist into adulthood. To better understand the exercise experience in MI, we determined the physiological and perceptual responses during and following a bout of exercise performed at different intensities typically experienced during sport in youth with MI. Thirty-eight adolescents (11-18 years) categorised on the Bruininks-Oseretsky Test of Motor Proficiency-2 Short-Form performed a peak oxygen uptake bike test ([Formula: see text]) test at visit 1 (V1). At visits 2 (V2) and 3 (V3), participants were randomly assigned to both low-intensity (LI) 30min exercise at 50% peak power output (PPO50%) and high-intensity (HI) 30s cycling at PPO100%, interspersed with 30s rest, for 30min protocol (matched for total work). Heart rate (HR) and rating of perceived exertion (RPE) for legs, breathing and overall was measured before, during and at 1, 3 and 7-min post-exercise (P1, P3, P7). There was a significant difference in [Formula: see text] between groups (MI:31.5±9.2 vs. NMI:40.0±9.5ml⋅kg-1⋅min-1, p<0.05). PPO was significantly lower in MI group (MI:157±61 vs. NMI:216±57 W)(p<0.05). HRavg during HI-cycling was reduced in MI (140±18 vs. 157±14bpm, p<0.05), but not LI (133±18 vs. 143±17bpm, p>0.05). Both groups experienced similar RPE for breathing and overall (MI:7.0±3.0 vs. NMI:6.0±2.0, p>0.05) at both intensities, but reported higher legs RPE towards the end (p<0.01). Significant differences were found in HRrecovery at P1 post-HI (MI:128±25.9 vs. NMI:154±20.2, p<0.05) but not for legs RPE. Perceived fatigue appears to limit exercise in youth with MI in both high and low-intensity exercise types. Our findings suggest interventions reducing perceived fatigue during exercise may improve exercise tolerance and positively impact on engagement in physical activities.